Comparative Study of the Catalytic Amination of Benzylic C–H Bonds Promoted by Ru(TPP)(py)2 and Ru(TPP)(CO). Issue 29 (18th September 2015) - Manca, Gabriele; Mealli, Carlo; Carminati, Daniela Maria; Intrieri, Daniela; Gallo, Emma
Abstract: A combined experimental and DFT‐based theoretical analysis elucidated the influence of the axial ligand L on the catalytic activity of Ru(porphyrin)L complexes in promoting the amination of benzylic C–H bonds by organic azides (RN3 ). Experimental data indicated that the catalytic activity of Ru(TPP)(CO) (1 ) (TPP = dianion of tetraphenylporphyrin) is comparable to that of Ru(TPP)(py)2 (2 ) (py = pyridine). DFT modelling disclosed that2 can be regarded as a precatalyst that becomes active after the endergonic loss of one pyridine ligand to give the unsaturated species [Ru](py) (11 ) [Ru] = Ru(porphine). This complex would react with RN3 to give the mono‐imido singlet complex [Ru](py)(NR)S (6S ), which can be easily transformed into the triplet isomer6T having diradical character at the imido N atom. The subsequent formation of the benzylic amine PhCH2 NHR occurs through a radical homolytic activation of one C–H bond of the toluene substrate (PhCH3 ). Conversely, by staying on the singlet potential‐energy surface, 6S can undergo dissociation of the pyridine ligand to form [Ru](NR). This complex can activate another RN3 molecule to form the bis‐imido compound [Ru](NR)2, which is also catalytically active. At this point, the mechanism becomes independent of the nature of the original ligand L coordinated to [Ru]. Abstract : The catalytic activity of Ru(TPP)(py)2 (2 ) (TPP = dianion of tetraphenylporphyrin, py = pyridine) in the amination of C–H bonds by organic azides (RN3 ) was experimentally compared to that of Ru(TPP)(CO) (1 ). A computational analysis corroborates similar radical mechanisms with a triplet imido intermediate, in spite of the electronic differences of the apical ligands.